The Influence of State Anxiety and Working Memory Capacity on Attention Control of High-level Athletes - Tianrui Xue; Tao Lyu; Tao Xue; Miao Yu; Tingting Fu; Hao Guo , (Revista de Psicología del Deporte (Journal of Sport Psychology), 2022)
Objective: The current study distinguishes study participants with low and high working memory capacity (WMC) (state anxiety), manipulating state anxiety situations in order to test the interference effect of state anxiety on attention control and the promotion of high WMC on attention control. Method: This study used a two-factor mixed design. The independent variable within the group is state anxiety (low, high), and the independent variable between the groups is WMC (low, high). The dependent variable is the level of attention control (Incubation period, saccade error rate). The covariate is trait anxiety (T-AI score). Results: The main effect of state anxiety is significant and the main effect of WMC is significant, but the interaction between the two is not significant. Conclusion: The benefit of WMC for attention control is cross-situational stability, and the key to attention control ability may, potentially, be working memory